Research progress on SiMOC coatings prepared by polymer pyrolysis and chemical vapor deposition. Issue 1 (31st December 2023) - Jing, Weichen; Tariq, Naeem ul Haq; Tang, Mingqiang
ABSTRACT: The SiOC materials have shown great potential for a number of engineering applications owing to their excellent physical and chemical properties. Due to the unique microstructure of SiOC coatings, different variants of polymer pyrolysis and chemical vapor deposition (CVD) processes are used to prepare SiOC coatings with different properties. However, in terms of their performance and potential for preparing variety of SiOC materials, a comparative study on these two methods has not been reviewed in a single article. Therefore, this article attempts to investigate the development of SiOC materials in recent years by comparing the two preparation methods. Furthermore, the research results of different types of SiMOC coatings, developed in past 20 years, have been critically discussed from three aspects, i.e. (1) the selection of precursor, (2) types of metal cationic additives, and (3) coating preparation methods. The in-depth study of SiMOC coatings suggests that irrespective of preparation method used to prepare SiMOC coatings, the selection of precursors can be divided into two broad categories: (a) polymer precursors and (b) organic precursors. Furthermore, it was revealed that by adding some metal elements (such as Al, Zr, HF, Ce, Ti, and Ta) to the precursor, some properties of SiOC coatings can be further improved. Therefore, the main disadvantages of the two preparation methods are: (1) the porosity problem when the polymer is converted to ceramics in polymer pyrolysis method and (2) the low deposition rate of the CVD method.